2021
DOI: 10.1186/s11671-021-03619-7
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Magnetic Properties of Cobalt-Doped FeMn2O4 Spinel Nanoparticles

Abstract: Mixed-metal oxide nanoparticles have attracted great scientific interest since they find applications in many fields. However, the synthesis of size-controlled and composition-tuned mixed-metal oxide nanoparticles is a great challenge that complicates their study for practical application. In this study, Co-doped FeMn2O4 nanoparticles were synthesized by the solvothermal method in which the crystallization was carried out under autogenous pressure at temperatures of 190 °C for 24 h. The influence of Co doping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…x 10 -2 and 5 x 10 -2 mbar respectively. These values, close to the theoretical one (8.511 Å), slightly increase with the deposition pressure, are consistent with previous studies reported in the literature [64]- [66]. The electrochemical behaviour of the different films exhibits quasi-rectangular CV curves at the various pressures, typically observed for a capacitive material (Fig.…”
Section: Tuning the Film Porosity With The Sputtering Deposition Pres...supporting
confidence: 92%
“…x 10 -2 and 5 x 10 -2 mbar respectively. These values, close to the theoretical one (8.511 Å), slightly increase with the deposition pressure, are consistent with previous studies reported in the literature [64]- [66]. The electrochemical behaviour of the different films exhibits quasi-rectangular CV curves at the various pressures, typically observed for a capacitive material (Fig.…”
Section: Tuning the Film Porosity With The Sputtering Deposition Pres...supporting
confidence: 92%
“…Additional interest in studying spinel ferrites is due to the possibility of tailoring the properties by cation substitution, increasing their practical application opportunities. In particular, the influence of various cations on the properties of Mn x Fe 3-x O 4 nanoparticles has been discussed in the literature, including the effect of La and Sm on photocatalytic properties [23,24]; Mo, Cr, and Zn on dielectric properties [25][26][27][28]; Cu, Co, and Dy on magnetic properties [29][30][31][32]; and so on. However, most studies have discussed the effect of substitution on the properties of the Mn x Fe 3-x O 4 system in the iron-rich region, especially on the properties of manganese ferrite, while the literature data on the study of the manganeserich region (x~2) are limited.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Mnbased spinels such as CoMn 2 O 4 , CuMn 2 O 4 and NiMn 2 O 4 were studied as OER catalysts. [19][20][21][22][23][24][25][26] It has been reported that MnFe 2 O 4 , one of the Fe-Mn spinels, is a stable OER catalyst. In such a magnetic ferrite, Mn ions mostly occupy A sites and Fe ions mainly occupy B sites.…”
Section: Introductionmentioning
confidence: 99%